2020
DOI: 10.3389/fgene.2020.00290
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of mRNAs and LncRNAs in Chronic Intermittent Hypoxia Exposure-Aggravated Atherosclerosis

Abstract: Atherosclerosis is the pathological basis of cardiovascular disease. Obstructive sleep apnea (OSA) aggravates atherosclerosis, and chronic intermittent hypoxia (CIH) as a prominent feature of OSA plays an important role during the process of atherosclerosis. The mechanisms of CIH in the development of atherosclerosis remain unclear. In the current study, we used microarray to investigate differentially expressed mRNAs and long non-coding RNAs (lncRNAs) in aorta from five groups of ApoE −/− mice fed with a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…In a study that analyzed the differential expression of mRNAs and long noncoding RNAs in atherosclerotic vascular tissues of ApoE −/− mice, markedly fewer genes were significantly upregulated in mice exposed to CIH for 12 weeks than in mice exposed to CIH for 8 weeks, which leads to weakening of atherosclerotic vascular tissue. The specific mechanism involved was related to the abnormal expression of heat shock proteins caused by CIH via the endoplasmic reticulum protein processing pathway [ 139 ]. This study also showed that the long-term CIH exposure resulted in reduced mRNA expression of Rev-erb (a member of the nuclear receptor superfamily that is important for the regulation of immunity, metabolic function, and circadian rhythm) and exacerbated the development of atherosclerosis, suggesting that Rev-erb may be involved in the development of CIH-related AS and play an important role in it.…”
Section: Pathophysiologic Mechanisms Underlying Osa-cih-induced Asmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study that analyzed the differential expression of mRNAs and long noncoding RNAs in atherosclerotic vascular tissues of ApoE −/− mice, markedly fewer genes were significantly upregulated in mice exposed to CIH for 12 weeks than in mice exposed to CIH for 8 weeks, which leads to weakening of atherosclerotic vascular tissue. The specific mechanism involved was related to the abnormal expression of heat shock proteins caused by CIH via the endoplasmic reticulum protein processing pathway [ 139 ]. This study also showed that the long-term CIH exposure resulted in reduced mRNA expression of Rev-erb (a member of the nuclear receptor superfamily that is important for the regulation of immunity, metabolic function, and circadian rhythm) and exacerbated the development of atherosclerosis, suggesting that Rev-erb may be involved in the development of CIH-related AS and play an important role in it.…”
Section: Pathophysiologic Mechanisms Underlying Osa-cih-induced Asmentioning
confidence: 99%
“…Oxidative Medicine and Cellular Longevity of heat shock proteins caused by CIH via the endoplasmic reticulum protein processing pathway [139]. This study also showed that the long-term CIH exposure resulted in reduced mRNA expression of Rev-erb (a member of the nuclear receptor superfamily that is important for the regulation of immunity, metabolic function, and circadian rhythm) and exacerbated the development of atherosclerosis, suggesting that Rev-erb may be involved in the development of CIHrelated AS and play an important role in it.…”
mentioning
confidence: 99%
“…Moreover, the differential expression levels of lncRNAs and mRNAs in atherosclerotic vascular tissue of CIH-exposed mice were screened. Changes were mainly an enrichment in the pathway of protein processing in the endoplasmic reticulum, which could ultimately turn to heat shock proteins, and their functions in protein folding may account for CIH aggravating atherosclerosis [140] …”
Section: Ncrna In Osamentioning
confidence: 99%
“…Changes were mainly an enrichment in the pathway of protein processing in the endoplasmic reticulum, which could ultimately turn to heat shock proteins, and their functions in protein folding may account for CIH aggravating atherosclerosis. [140] Conclusions and future directions…”
Section: Mirna In Osa Related To Phtmentioning
confidence: 99%
“…Another report depicted the profiling of mRNAs and lncRNAs in the aorta when treated with IH. The description of this system may provide potential candidates for future research on IH-induced AS ( 46 ). In addition, its unique RNA was also explored to understand its function.…”
Section: Mechanismmentioning
confidence: 99%